DETERMINAN FAKTOR-FAKTOR YANG BERKONSTRIBUSI TERHADAP PERUBAHAN EKSPOR KOPI INDONESIA KE MALAYSIA TAHUN 2008-2022 - Dian Hafizah; Lailatul Rahmi (Jurusan Agribisnis, Fakultas Pertanian, Perikanan dan Biologi Universitas Bangka Belitung, 2023)
The aim of the research is to analyze the influence of the amount of coffee production in Indonesia, the area of Indonesian coffee land, the variable changes in the rupiah and the inflation rate on the amount of Indonesian coffee exports to Malaysia during the period 2008 to 2022. This research was conducted using quantitative descriptive methods using time series data 2008-2022.Types of data include the volume of Indonesian coffee exports to Malaysia, the amount of production and area of Indonesian coffee land, changes in the rupiah against the US dollar (exchange rate), and inflation. Data analysis used multiple linear regression analysis using Eviews12 software. Based on the results, it was found that partially Indonesian coffee production, Indonesian coffee land area and inflation did not significantly influence the amount of Indonesian coffee exports to Malaysia in 2008-2022. The partial change in the value of the Indonesian currency has a significant impact on the amount of Indonesian coffee exports to Malaysia in 2008-2022. Simultaneously, Indonesian coffee production, Indonesian coffee land area, rupiah exchange rate and inflation have a significant influence and are able to explain the volume of Indonesian coffee exports to Malaysia in 2008-2022 of 48.8878%.